Students' Perception of Premarital Sexual Behavior among Adolescents and Implications for Guidance and Counseling Services - Lusi Elvita Sari; Yeni Karneli (Jurnal Neo Konseling, 2019)
Premarital sexual behavior done teenagers was very alarming and widespread the talk in various media such as radio, television, newspapers, and media Online others. At this time there have been changes in the views and sexual behavior of the community. Among teenagers today, there are students who consider some of the sexual behaviors such as holding hands and hugging, which are common things and the behavior of holding hands and hugging is often seen in general. This study aims to describe students' perceptions of premarital sexual behavior in various forms. This study uses a descriptive approach with quantitative methods. The population of this study was SMA N I Kubung high school students. The instrument used in this study was a questionnaire. The data obtained was analyzed using percentage techniques through the Microsoft Office Excel program.The results of the study revealed that students' perceptions of premarital sexual behavior among adolescents in general tend to be classified as poor with a percentage of 48.89%. This study has limitations in collecting data, content or variables included in the category are sensitive enough to be discussed.